Conceptualizing Muslim identity in the US, post-9/11 - Maretha Dellarosa (Indonesian Journal of Islam and Muslim Societies, 2022)
This article examines the conception of Muslim identity by Muslim teachers in the broader Islamophobic American social environment and the ways they support young Muslim children. To answer these questions, this article employs a qualitative case study by observing and interviewing Muslim teachers who teach kindergarteners in a Sunday school program. Drawing on identity, social identity, and intersectionality as theoretical frameworks, the findings from this study demonstrate that the interpretation of good Muslim and Islamic principles serve as an instrument to conceptualize Muslim teachers’ identity.